Sistem Parkir Mobil Otomatis Untuk Kondisi Parkir Paralel - Singgih Bima Prakoso (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2015)
Abstract - This study will focus on the design of automatic parallel parking systems. The parking system is designed for small cars that use Arduino Mega 2560, HC-SR04 ultrasonic sensor, optocoupler, DC motor and servomotor. The ultrasonic sensor and optocoupler SR-04 is the input (input) of this system that will be processed by the ATmega 2560 microcontroller. Each input will be processed by the microcontroller to determine the amplitude and direction of rotation of the servomotor in driving the car. This automatic parking system starts when the vehicle searches for a parking space that matches the specified size, and then maneuvers into the parking space. The work cycle of the PWM is the main element of speed control of a DC motor. The results of testing the system in stages starting from the forward detecting the parking space until backwards to do the parking process is done to get the size of the parking space as well as the ideal distance for parking as a whole which is Â± 70 cm and Â± 35 cm wide. The results showed that, first, the automatic parking system for parallel parking left and right worked well with an average success rate of 80% for space detection and 48% for left parking, 85% for space detection and 45% for parking at right side to finish with a size of 70 cm of parking space and 35 cm wide. Keyword : automatic parking, parallel parking left and right, counter parking